NILAI KOMUNIKASI ISLAM PADA TRADISI MAPPADENDANG DI DESA LANCIRANG KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Abd. Rahim Arsyad; Muhammad Saleh; Muhammad Jufri (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2018)
This research focuses on studying the meaning of Mappadendang tradition, how the method of communicating the message of the communication to the tradition of Mappadenddang and how the value of Islamic communication in the Mappadendang tradition is found in Lancirang village. The purpose of this study is to find out the meaning of Mappadendang tradition, to know the method of delivering Islamic communication and to know the value of Islamic communication in the tradition of Mappadenddang in Lancirang village The results of the study show that the Mappadendang tradition is a hereditary tradition and thanks to the community in the village of Lancirang, which has a meaning to strengthen the relationship between the community and farmers. So that the delivery of the traditional communication message can be known by the community around Lancirang village by implementing tudang sippulung and circulating invitations from the formation of the committee, which has the value to introduce and preserve the cultural values of these children towards the relevant in accordance with Islamic teachings.